STRATEGI, TEKNOLOGI INFORMASI DAN PENGEMBANGAN UKM DI ERA OTONOMI DAERAH - ., Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
Â  Abstract The Among careful proper of statement of John Naisbitt: Think Globally locally act and which is implementation by Morihiko Hiramatsu, Governor Oita, Japan become password work One-Village, One Product Movement (movement one countryside one product) used as by frame to develop local excellence which orient global market. Undeniable is true problem of performance oftentimes become constraint or bogey at small and medium industry sector to expand. With existence of progress of technology and science expected can assist the make-up of performance. One of the exploiting of the technology is usage of technology base on information (TI). With existence of progress of technology and science expected can assist the make-up of performance Hence solution able to be conducted to push growth and improvement of performance of UKM is needing the existence of real step of usage of TI so that/ to be can be competitive with big scale company in this case it is of course TI have to earn to be used as by appliance able to improve performance productivity and advantage maximization profit to UKM. Some anticipated factor have important role in spreading of TI one of them is support and role of government agency. Hereinafter according to King role of the institute in this case is as vendor of information about technological innovation, owner of authority of regulation, as provider of aid of financial, executor research into and inwrought development, and protector to ownership of copyrights. Some idea model trying to join local excellence (internal environment) and global market opportunity (external environment) in business, require to be tried with a few adjustment with condition of existing objective to develop UKM in face of free market in autonomous framework of area. Keywords: Strategic, Globalization, Autonomous of Area, Information Technology, Small and Medium Industry, Science and Technology.